The social constructions and experiences of madness - Santos, Monika Maria Lucia Freitas dos; Pelletier, Jean-François (At the interface, 2018)
Over the course of the centuries the meanings around mental illness have shifted many times according to societal beliefs and the political atmosphere of the day. The way madness is defined has far reaching effects on those who have a mental disorder, and determines how they are treated by the professionals responsible for their care, and the society of which they are a part. Although madness as mental illness seems to be the dominant Western view of madness, it is by no means the only view of what it means to be 'mad'. The symptoms of madness or mental illness occur in all cultures of the world, but have different meanings in different social and cultural contexts. Evidence suggests that meanings of mental illness have a significant impact on subjective experience; the idioms used in the expression thereof, indigenous treatments, and subsequent outcomes. Thus, the societal understandings of madness are central to the problem of mental illness and those with the lived experience can lead the process of reconstructing this meaning